Two Step and Newton- Raphson Algorithms in the Extraction for the Parameters of Solar Cell - RASHEED, Mohammed; SHIHAB, Suha; RASHID, Taha (Al-Qadisiyah Journal of Pure Science, 2021)
The goal of this work is to find a numerical solution of nonlinear solar cell equation. This equation has been instructed using a single-diode model. The proposed method consists of solving the equation using two iterative methods with the initial value . Moreover, the Newton’s and Two-step methods are used to determine the required the current, the voltage, and the power of the PV cell in the procedure of the present research. Different values of load resistance have introduced with these methods. The obtained results appeard that the proposed method is the most efficient compare with NRM and all the calculations are achieved using Matlab program.